2021
DOI: 10.15587/1729-4061.2021.230113
|View full text |Cite
|
Sign up to set email alerts
|

Devising a model of the airflow with dust particles in the intake system of a vehicle’s internal combustion engine

Abstract: This paper considers the mechanism of malfunction of internal combustion engines that implies the accelerated local wear of parts in individual cylinders as a result of uneven distribution of dust particles that pass through the air filter in the intake system. In order to acquire quantitative data on the effect of the structure of the intake system on the redistribution of dust in engine cylinders, the two-phase flow of air with dust particles in the standard elements of the intake system was mathematically m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…It follows that the proposed model qualitatively corresponds to the studied process of loading parts with loads that are not provided for in the design of the engine and are caused by a violation of operating conditions. Such tasks are considered and solved in a set of expert research methods, including for other components and systems of engines, by developing models applicable under abnormal conditions and loads [26].…”
Section: Discussion Of the Results Of Modeling The Destruction Of Par...mentioning
confidence: 99%
“…It follows that the proposed model qualitatively corresponds to the studied process of loading parts with loads that are not provided for in the design of the engine and are caused by a violation of operating conditions. Such tasks are considered and solved in a set of expert research methods, including for other components and systems of engines, by developing models applicable under abnormal conditions and loads [26].…”
Section: Discussion Of the Results Of Modeling The Destruction Of Par...mentioning
confidence: 99%
“…On the other hand, the authors of the paper [114] believe that the wear of the friction pair "cylinder-piston rings" and thus the durability of the internal combustion engine depends not only on the efficiency of the inlet air filtration and the wear resistance of the parts, but also on the design of the intake manifold. In the intake manifold of a multicylinder car engine (Figure 35a), due to the rapid twisting of the flowing air in the ducts and the associated effect of the inertial force on the dust particles, uneven distribution of the dust particles to the individual engine cylinders can occur, resulting in uneven wear of the piston-cylinder group.…”
Section: Components Of Dust Percent By Weight [%]mentioning
confidence: 99%
“…In the intake manifold of a multicylinder car engine (Figure 35a), due to the rapid twisting of the flowing air in the ducts and the associated effect of the inertial force on the dust particles, uneven distribution of the dust particles to the individual engine cylinders can occur, resulting in uneven wear of the piston-cylinder group. Simulation studies were carried out in the air velocity range of 5-20 m/s in branched manifold channels with diversion angles of 45°, 90°, and 135° for the most characteristic particle sizes of 5-30 μm [114,115]. The computational results showed that the dust particles deviate from the air flow line due to inertia and can move through the side outlet the larger the particle size, channel deflection angle and air velocity-Figure 35b.…”
Section: Components Of Dust Percent By Weight [%]mentioning
confidence: 99%
See 1 more Smart Citation